Diversity and Abundance of Insects Pollinator of Chayote (Sechium edule (Jacq.) Swartz - Muhammad Dzaky Alfawwaz; Agus Dana Permana; Ramadhani Eka Putra (Jurnal Biodjati, 2022)
Chayote plants (Sechium edule) with monoecious characters require a pollination process. The pollination process requires pollinating agents to increase its productivity, one of which is insects. This research aimed to determine the diversity and abundance of insects pollinator on chayote plants. Observation of diversity and abundance used a scan sampling method. Pollinator insects observations were carried out in 3 time periods, morning, afternoon, and evening on male and female flowers. We measured environmental parameters such as temperature, humidity, wind speed, and light intensity. Eight species of wild insects pollinated chayote flowers, Apis cerana, Apis dorsata, Lasioglossum leucozonium, Polistes sagittarius, Phimenes flavopictus, Campsomeriella annulata, Lucilia sericata, and Musca domestica. The insect pollinators community had moderate diversity (1.23), a relatively dynamic community (0.59), and moderate dominance (0.62), with A. cerana, which had been the dominant insect pollinator with a relative abundance of 61.63%. Musca domestica and L. sericata were (0,58%) the least dominant insect pollinator with a relative abundance of 0.58%. This research concludes that the insects pollinator of chayote has a moderate level of diversity, relatively dynamic community, and average dominance.